Evaluating the corrosion resistance of ubm-deposited cr/crn multilayers (2011)
This work was aimed at evaluating the corrosion resistance of multilayer Cr/CrN coatings deposited by the unbalan-ced magnetron sputtering (UBM) technique. Coatings were produced at room temperature using 400 mA discharge current, 9 sccm argon flow and 3 sccm nitrogen flow. The total thickness of coatings deposited on AISI 304 stainless steel and silicon (100) varied between 0.2 a 3 μm as bilayer period varied between 20 and 200 nm. Coating microstructure and chemical composition was stu-died through scanning electron microscopy (SEM) and tex-ture and crystalline phases were analysed by X-ray diffraction (XRD) before and after corrosion tests which were carried out by potentiodynamic polarisation using 0.5 M H2SO4 + 0.05M KSCN solution. Lower bilayer period coatings presented better corrosion resistance and their corrosion mechanism is discussed in this article.